Optimization of Student Needs Analysis Instruments for the Development of AI-Based History Learning Videos at SMA Negeri 1 Indralaya: Optimization of Student Needs Analysis Instruments for the Development of AI-Based History Learning Videos at SMA Negeri 1 Indralaya - devita, Devita Septia Ningsih; Syarifuddin , Syarifuddin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Optimizing the analysis of learner needs is a crucial stage in the development of artificial intelligence (AI)-based history learning videos. With proper analysis, the development of learning videos can be adjusted to user needs, both in terms of material, delivery methods, and AI-based interactive features. This article discusses the role of needs analysis in the development of AI-based history learning videos, including identifying user needs, mapping appropriate technology, and its impact on the effectiveness of history learning. The methods used in this study include interviews, observations, and literature studies. The results of the study show that a comprehensive needs analysis can increase the relevance, engagement, and understanding of learners in AI-based learning. By understanding learners' needs in depth, developers can create learning videos that are more effective, interesting, and in line with technological developments.